2014
DOI: 10.1016/j.vhri.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Models to Predict the Burden of Cardiovascular Disease Risk in a Rural Mountainous Region of Vietnam

Abstract: The Asian and CMCS models provided similar results in predicting CVD risk in the Vietnamese population in Thai Nguyen. The Framingham model provided vastly different results. The suggestion may be that for the specific Vietnamese setting, the Asian and CMCS models provide most valid and reliable results; however, this has to be investigated in further analyses using real-life data for potential confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…For example, there was no model to predict CVD risk or relative risk of treatment versus no treatment for hypertension or CVD. However, we had previously shown that an existing Asian model may be appropriate to predict CVD in Vietnam, as used in this study [14]. We also applied the results from a meta-analysis among Asian studies, which seems reasonable to weight the different CVD components and estimate the RR of treatment for HBP [3].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, there was no model to predict CVD risk or relative risk of treatment versus no treatment for hypertension or CVD. However, we had previously shown that an existing Asian model may be appropriate to predict CVD in Vietnam, as used in this study [14]. We also applied the results from a meta-analysis among Asian studies, which seems reasonable to weight the different CVD components and estimate the RR of treatment for HBP [3].…”
Section: Discussionmentioning
confidence: 99%
“…We previously conducted community screening for hypertension among currently untreated, undiagnosed adults aged 35-64 years, measuring BP during two visits [14]. Individual cases with BP in the hypertensive range were confirmed by a doctor at the CHS.…”
Section: Screening and Hypertension Managementmentioning
confidence: 99%
See 3 more Smart Citations